Screening for small‐for‐gestational‐age fetuses. (26th November 2019) - Hansen, Ditte N.; Odgaard, Helle S.; Uldbjerg, Niels; Sinding, Marianne; Sørensen, Anne
Abstract: Introduction: It is well established that correct antenatal identification of small‐for‐gestational‐age (SGA) fetuses reduces their risk of adverse perinatal outcome with long‐term consequences. Ultrasound estimates of fetal weight (EFWus ) are the ultimate tool for this identification. It can be conducted as a "universal screening", that is, all pregnant women at a specific gestational age. However, in Denmark it is conducted as "selective screening", that is, only on clinical indication. The aim of this study was to assess the performance of the Danish national SGA screening program and the consequences of false‐positive and false‐negative SGA cases. Material and methods: In this retrospective cohort study, we included 2928 women with singleton pregnancies with due dates in 2015. We defined "risk of SGA" by an EFWus  ≤ −15% of expected for the gestational age and "SGA" as birthweight ≤−22% of expected for gestational age. Results: At birth, the prevalence of SGA was 3.3%. The overall sensitivity of the Danish screening program was 62% at a false‐positive rate of 5.6%. Within the entire cohort, 63% had an EFWus compared with 79% of the SGA cases. The sensitivity was 79% for those born before 37 weeks of gestation but only 40% for those born after 40 weeks of gestation. The sensitivity was also associated with birthweight deviation; 73% among extreme SGA cases (birthweight deviation ≤−33%) and 55% among mild SGA (birthweight deviation between −22% and −27%). False diagnosis of SGA was associated with an increased rate of induction of labor (ORadj  = 2.51, 95% CI 1.70‐3.71) and cesarean section (ORadj  = 1.44, 95% CI 0.96‐2.18). Conclusions: The performance of the Danish national screening program for SGA based on selective EFWus on clinical indication has improved considerably over the last 20 years. Limitations of the program are the large proportion of women referred to ultrasound scan and the low performance post‐term.